Performance validation of a Remotely Monitored Off-Grid PV Plant in UTP - Ogail Abdelsalam Elhassan, Ali (IRC, 2017)
Constant burning of fossil fuels for power generation not only depletes our reserves of non-renewable energy but does carry detrimental harm to the environment and world climate. Hence, there’s a growing need for sufficient and friendly environmental sources of energy. Solar energy or energy from the “Sun” presents an ideal alternative for its sustainability and ability to reaching remote “Off-grid” locations. This research work investigates an off-grid photovoltaic (PV) power plant in Universiti Teknologi PETRONAS, Perak, Malaysia. The plant’s performance was validated through theoretical calculations and cross-comparing the outcome with previous data recordings performed by “Sunny Portal” web monitoring service of the same month. The obtained results were found to supplement the pervious study. Conclusive results were achieved through regular system updates, taking targeted measurements based on observed data trends from previous studies with an 8.4% error obtained, while 13:00-14:00 appear to be best times for energy production as solar insolation is at peak.